2021
DOI: 10.1080/14756366.2021.1999237
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based virtual screening and biological evaluation of novel small-molecule BTK inhibitors

Abstract: Bruton tyrosine kinase (BTK) is linked to multiple signalling pathways that regulate cellular survival, activation, and proliferation. A covalent BTK inhibitor has shown favourable outcomes for treating B cell malignant leukaemia. However, covalent inhibitors require a high reactive warhead that may contribute to unexpected toxicity, poor selectivity, or reduced effectiveness in solid tumours. Herein, we report the identification of a novel noncovalent BTK inhibitor. The binding interactions (i.e. interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Using structure-based virtual screening, Lin et al recently found novel small molecule inhibitors of Bruton tyrosine kinase (BTK). [97] Binding contacts within BTK were found by docking known inhibitors with probable biological activity, and these proteinligand interactions were then exploited for virtual screening of NCI database compounds (0.28 million). Using the Lipinski Rule of Five and PAINS substructures, the database compounds were filtered, and the remaining compounds were docked into the active site of BTK.…”
Section: Structure-based Approachesmentioning
confidence: 99%
“…Using structure-based virtual screening, Lin et al recently found novel small molecule inhibitors of Bruton tyrosine kinase (BTK). [97] Binding contacts within BTK were found by docking known inhibitors with probable biological activity, and these proteinligand interactions were then exploited for virtual screening of NCI database compounds (0.28 million). Using the Lipinski Rule of Five and PAINS substructures, the database compounds were filtered, and the remaining compounds were docked into the active site of BTK.…”
Section: Structure-based Approachesmentioning
confidence: 99%